Management of pregnancy and delivery in women with transposition of the great arteries after atrial switch operation: A 16‐year single‐center experience. Issue 2 (12th December 2021) - Harada, Gen; Inai, Kei; Shimada, Eriko; Ishido, Mikiko; Shinohara, Tokuko; Ogawa, Masaki
Abstract: Aim: This study aimed to summarize cases of successful pregnancy and delivery in patients with transposition of the great arteries (TGA) after atrial switch operation (ASO), to provide management, clinical experience, and maternal and fetal outcomes. Methods: During a 16‐year period (2004–2019), we experienced 30 pregnancies in 15 patients after ASO at our institution. We retrospectively reviewed the medical records of the patients. Results: In 30 pregnancies, there were 21 (70%) live births, five (17%) miscarriages, and four (13%) artificial abortions. There were no maternal or neonatal deaths. Cardiac complications occurred in nine (43%) patients: deterioration of right ventricular (RV) function in one, symptomatic heart failure (HF) in three, supraventricular tachyarrhythmia requiring electrical cardioversion in two, sick sinus syndrome that required pacemaker implantation in two, and hemoptysis in one. Obstetric complications occurred in five (24%). Neonatal complications were premature births (delivery at <37 weeks of gestation) in 15 (71%), and birthweight <2500 g in 18 (86%). The mode of delivery consisted of vaginal delivery (VD) in five (24%), and cesarean section (CS) in 16 (76%). Conclusion: A high incidence of preterm CS and cardiac complications including deterioration of RV function was observed in patients who had undergone ASO for TGA.